Ethnomathematics in the Jonggan Art of the Dayak Kanayat’n - Rino Sinus Pandanu (Universal Education, 2024)
This study explores the role and presence of ethnomathematics in jonggan, a traditional art form of the Dayak Kanayat’n community. Jonggan is a social dance involving dancers, musicians, and singers that reflects the community's rich cultural heritage. This study employs a qualitative approach through a literature review to identify mathematical concepts embedded in the patterns, rhythms, and choreography of jonggan. The findings reveal the presence of geometric forms such as triangular and rectangular prisms, circles, and trapezoids, as well as numerical sequences in the dance movements and musical instruments. These elements not only enrich the aesthetic structure of jonggan but also serve as a medium for transmitting cultural knowledge. The study concludes that integrating ethnomathematical elements into mathematics education can create a more engaging and culturally relevant learning experience. By illustrating how mathematics is inherent in Dayak Kanayat’n traditions, this research contributes to a deeper understanding of the intersection between culture and mathematics and supports the development of contextualized learning strategies.